Actor-Network Theory approach in aligning divergences in policies governing rural tourism in Semporna, Sabah - Siow, May Ling (2014)
The purpose of this thesis is to formulate a framework for rural tourism policies in Semporna, Sabah, Malaysia. This study is carried out in response to current anthropogenic issues occurring at the study site. The objectives of the study is (i) to identify emerging themes of policies governing rural tourism, (ii) to determine elements influencing effective policy governance in rural tourism and (iii) to identify responsible tourism indicators for rural tourism policies in Semporna, Sabah. The study adopts a full qualitative approach through the lens of a constructivist, employing Actor Network Theory. This highlights the holistic approach of the human and non-human continuum. The study elicits data from three sources namely, policymakers, end-user of the policy and policy text corpus. The study involves the collection of primary data through the Delphi Policy technique for policy makers, in-depth interviews for end-users of the policy and text analysis for policy text corpus. All findings is analysed using the thematic analysis approach and triangulated. The significant contributions that have emerged from this study in addressing responsible rural tourism policies in Semporna Sabah includes; (i) methodological contributions; modified policy Delphi technique, (ii) theoretical contributions that is the dynamic framework of responsible rural tourism, (iii) decision making contributions that is the analytical network policy process and (iv) transferable qualitative indicators. This indicates that the main aspects of rural tourism policies comprising of economic, social and environment factors must not be assumed in isolation and evolves around human and non-human continuum. The thesis provides insightful qualitative analysis on the divergence governing rural tourism policies in Semporna, Sabah. The findings will be very useful for future formulation of rural tourism policies especially in the context of marine tourism involving heterogeneous actors. This thesis can act as a point source for future tourism policy research as it has been the biggest challenge and limitation to date in retrieving the extant policy documents. The significance of the findings could enable policy makers to set agendas, formulate, adopt, implement and evaluate policies based on the guidelines of the framework. In addition, the emergent indicators would be useful in assessing the health of tourism policies in other rural tourism destinations.